THE INFLUENCE OF POLITICAL STABILITY AND ECONOMIC STABILITY ON THE INFLOW OF FOREIGN CAPITAL IN BOSNIA AND HERZEGOVINA - Šušić, Ilija; Šušić, Milan; Dragić, Darija (Journal of process management and new technologies, 2019)
With the Fourth Industrial Revolution (4IR), humanity has entered a new stage of development. The 4IR has become a reality for millions of people around the world, creating new business opportunities, governments and individuals. Nevertheless, it threatens the new political disagreements and contradictions within and between economies and societies. The combination with rising inequalities and geopolitical turmoil has stirred citizens' concerns about globalization and has provoked divided political opinions. Although world economic growth has been stronger over the past two years, the situation in the current changing economic and political context remains fragile. The World Economic Forum introduced the new Global Competitiveness Index 4.0 (GCI), a highly needed compass, based on a 40-year long experience of analyzing long-term competitiveness drivers. The results of the global competitiveness index provide impartial information that enables leaders in the public and private sectors to better understand and shape their strategies in the era of the fourth industrial revolution. The paper presents a detailed profile of the economy of Bosnia and Herzegovina as well as tables with global ranking data with all indicators. Using quantitative methods and data from survey surveys, the Competitiveness Report ranks countries based on a combination of 98 indicators grouped in 12 pillars of competitiveness.